Peran Guru dalam Kurikulum Merdeka: Upaya Penguatan Keterampilan Abad 21 Siswa di Sekolah Dasar - Noptario Noptario; Nikentari Rizki; Nur’aini Nur’aini; Effiana Cahya Ningrum (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The independent curriculum is very oriented to the activeness of students in participating in learning, so that the role of teachers in the independent curriculum is different from the curriculum that focuses on teachers as the main source of learning. In the implementation of an independent curriculum, the teacher is only a facilitator by directing and guiding students to learn according to their interests and desires. The purpose of this study is to analyze what teachers do in the implementation of the independent curriculum as an effort to strengthen students' 21st century skills. This research uses a qualitative research approach with Field Research research methods. Meanwhile, the data collection technique in this study used in-depth interviews to explore information about the role of teachers in implementing the independent curriculum. The resource persons in this study were the deputy head of curriculum and class teachers. While the data analysis techniques used in this study use thematic data analysis with stages of understanding data, coding data and determining themes. The role of teachers in the implementation of the independent curriculum as an effort to strengthen 21st century skills in elementary schools is carried out in various ways, ranging from conducting diagnostic assessments, implementing differentiated learning, integrating technology in learning, learning facilitators and implementing project-based learning. While the implications that will be felt by students in the efforts made by the teacher, include increasing the ability to think critically, increasing the ability to cooperate and collaborate, establishing good communication with other students, learning according to interests and desires and improving problem-solving skills.